MIKROALGA (CHLORELLA, SP.) SEBAGAI AGENSIA PENAMBAT GAS KARBON DIOKSIDA - Mulyanto, Adi (Jurnal Hidrosfir Indonesia, 2010)
This experiment was conducted to respon the issue of global warming where carbon dioxide emmited from burning fossil fuel was expected to be the reason. The experiment was performed at Institute for Environmental Technology, Puspiptek, Serpong within 35 days. Algae (Chlorella, sp.)was cultivated in a raceway type pond. The pond has effective volume of 1000 liters provided with agitator and located in a roofed area. Basic machanism of the CO2 sequestration was photosynthesis process, where chlorophyl, water, CO2, and sun light should be present. Reasearch result identified that algae has high capability for carbon dioxide (CO2) sequestration. Therefore, algae can be utilized as an agent for carbon sink. CO2 utilized was come from commercial CO2 tank which was available in the local market and has concentration of about 45%. During experiment, the culture was fed with gradually increasing of CO2 concentration, namely 5.91%, 8.18%, and 9.16%. The macro and micro nutrients were also added into the culture. CO2 absorption by the culture in average only reached 5.34%. therefore, the increasing of CO2 fed into the culture decreased theefficiency of CO2 absorbed. During the experiment, the growth of microalgae was also elaborated.